Hepatectomia regrada por videolaparoscopia - Kalil,Antonio Nocchi (1998)
With the improvement of laparoscopic techniques, endoscopic liver surgery has become feasible. While laparoscopic wedge liver resection are performed more frequently, laparoscopic (anatomical or nonanatomical) liver resection are still at an early stage of development and are somewhat controversial. We reporte laparoscopic hepatic resection without use of sophisticated laparoscopic instruments. A 47-year-old woman underwent radical mastectomy for adenocarcinoma in 1995. 1n the postoperative follow-up presented, a lesion in the left hepatic lobe and, after laparoscopic approach, left lateral segmentectomy was performed. The hepatic resection elapsed without complications. The surgical time was 4 hours and the blood loss was minimal, without transfusion being necessary.The abdominal drain was removed in 24 hours and the patient was discharged in the second postoperative day. Compared to the classic approach by laparotomy, this method was less traumatic, required a shorter hospital stay, and followed by faster recovery.